2002
DOI: 10.1038/sj.bjc.6600323
|View full text |Cite
|
Sign up to set email alerts
|

Higher expression of human kallikrein 10 in breast cancer tissue predicts tamoxifen resistance

Abstract: The human tissue kallikreins are secreted serine proteases, encoded by a group of homologous genes clustered in tandem on chromosome 19q13.3-4. Human kallikrein 6 and human kallikrein 10 are two new members of this family. Recently, we developed highly sensitive and specific immunofluorometric assays for human kallikrein 6 and human kallikrein 10, which allow for their quantification in tissue extracts and biological fluids. Both human kallikrein 6 and human kallikrein 10 are found to be down-regulated in brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 37 publications
1
30
0
1
Order By: Relevance
“…More precisely, KLK10 protein tissue accumulation was revealed to be an independent biomarker, predicting patients' resistance to tamoxifen treatment. Higher KLK10 tissue levels have been correlated with stronger resistance to tamoxifen, indicating the need for a redesign of the initial therapeutic scheme (Luo et al, 2002). Moreover, similar conclusions, regarding tamoxifen resistance, can also be drawn by the assessment of higher cytosolic PSA/KLK3 concentration in primary BC (Foekens et al, 1999).…”
Section: Klks As Cancer Monitoring Biomarkerssupporting
confidence: 55%
See 1 more Smart Citation
“…More precisely, KLK10 protein tissue accumulation was revealed to be an independent biomarker, predicting patients' resistance to tamoxifen treatment. Higher KLK10 tissue levels have been correlated with stronger resistance to tamoxifen, indicating the need for a redesign of the initial therapeutic scheme (Luo et al, 2002). Moreover, similar conclusions, regarding tamoxifen resistance, can also be drawn by the assessment of higher cytosolic PSA/KLK3 concentration in primary BC (Foekens et al, 1999).…”
Section: Klks As Cancer Monitoring Biomarkerssupporting
confidence: 55%
“…Stronger KLK4 ovarian cancer tissue staining has been observed in patients more resistant to paclitaxel administration, revealing the significance of this peptidase in stratifying patients for paclitaxel-based chemotherapy (Xi et al, 2004). Moreover, presurgically higher KLK10 serum concentrations have been found to be significantly correlated with ovarian cancer patients' poor response to chemotherapy (Luo et al, 2002). Contrary to KLK10, higher KLK11 and KLK13 tissue protein levels are more frequently associated with women showing an enhanced clinical response to chemotherapy, suggesting that this treatment option is suitable and effective for these patients, whereas the combination of the assessment of KLK6 and KLK8 tissue levels with those of KLK13 yields an enhanced monitoring potential (Borgono et al, 2003;Zheng et al, 2007).…”
Section: Klks As Cancer Monitoring Biomarkersmentioning
confidence: 85%
“…For patients with advanced breast cancer, a very limited number of studies (all from our laboratory) addressing the relation of serine proteases with the efficacy of systemic treatment are available. In this respect, we showed that high tumour levels of uPA (Foekens et al, 1995), kallikrein 3 , or kallikrein 10 (Luo et al, 2002) were significantly associated with a poor rate of response to tamoxifen therapy. In the present study, we investigated the predictive value of PMN-E for the efficacy of tamoxifen and chemotherapy in patients with advanced breast cancer.…”
Section: Discussionmentioning
confidence: 76%
“…For breast cancer patients who received systemic therapy for advanced disease, only three studies are available relating the levels of serine proteases, that is, uPA (Foekens et al, 1995), human kallikrein 3 (PSA) , or human kallikrein 10 (Luo et al, 2002) to a poor efficacy of first-line tamoxifen treatment. With respect to the predictive value of serine proteases for response to chemotherapy in advanced breast cancer, no published studies are yet available.…”
mentioning
confidence: 99%
“…Furthermore, a number of preliminary analyses suggest that certain kallikreins including KLK3 (Yu et al, 1995;Yu et al, 1998;Foekens et al, 1999), KLK5 (Yousef et al, 2002b(Yousef et al, , 2003cDiamandis et al, 2003), KLK7 (Talieri et al, 2004), KLK9 (Yousef et al, 2003a), KLK10 (Luo et al, 2002), KLK13 (Chang et al, 2002), KLK14 , KLK15 (Yousef et al, 2002c) may possess clinical utility as diagnostic, prognostic or predictive breast cancer biomarkers. For recent reviews on the human kallikrein family please see references Clements et al, 2004).…”
mentioning
confidence: 99%